2020
DOI: 10.1007/s10389-020-01313-z
|View full text |Cite
|
Sign up to set email alerts
|

Stress and burnout in health care workers during COVID-19 pandemic: validation of a questionnaire

Abstract: Aim To validate a questionnaire to assess stress and burnout in healthcare workers during COVID-19 pandemic. Subjects and methods In this study, content validity, Cronbach's alpha, and test-retest reliability method were utilized among 60 HCWs to evaluate the validity, internal consistency, and reliability of the questionnaire respectively. The final questionnaire was composed of four parts asking for the background information, questions about the stress caused by the COVID-19, the Depression, Anxiety and Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
137
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(166 citation statements)
references
References 27 publications
9
137
0
8
Order By: Relevance
“…The role of HCWs as "heroes" and their best practice in a dramatic, pandemic context have been often enhanced by widespread media reports of fatigue and burnout [14,15].…”
Section: Characteristics Of Hcws Who Were Infected By Sars-cov-19mentioning
confidence: 99%
“…The role of HCWs as "heroes" and their best practice in a dramatic, pandemic context have been often enhanced by widespread media reports of fatigue and burnout [14,15].…”
Section: Characteristics Of Hcws Who Were Infected By Sars-cov-19mentioning
confidence: 99%
“…Manual Therapists trained to specialise in the provision of fascia focused treatments are ideally placed to provide appropriate therapeutic interventions to help resolve resulting adhesive effects of respiratory and vascular secretions [16]. Studies support the efficacy of fascia focused manual interventions which not only improve gliding of tissues but also restore normal levels of hyaluronan [32,33]. This review identified a connection between fascia and serum interleukins IL-6, IL-8, tumour necrosis factor [TNF]-α and IL-1β, hyaluronan and the pathophysiology of severe acute respiratory syndrome [SARS] [21,22] and, importantly, an under-reported aspect of COVID-19, the development of inflammation of the superficial fascia due to an abnormal amassing of eosinophils [30].…”
Section: Introductionmentioning
confidence: 99%
“…Each item was rated on a scale of always/to a very high degree (100), often/to a high degree (75), sometimes/somewhat (50), seldom/to a low degree (25) and never/to a very low degree (0) (22). CBI has also been validated in pandemic context with Cronbach coefficient alpha of 0.94 (23). For this study, we used the Malay translated CBI (CBI-M) where it has been validated with Cronbach coefficient alpha of 0.83 to 0.87 (24).…”
Section: Introductionmentioning
confidence: 99%